A point prevalence survey and monitoring indicator research on the second batch of national key monitoring and rational use drugs - Tang, Li; Liu, Hongmei; Wu, Shasha; Liu, Jing; Jiang, Xiaoyu; Fu, Yuanyuan; Tao, Na; He, Yong (Frontiers in Pharmacology, 2024)
Background: With the remarkable effect of controlling the increase in drug costs by the 1 st batch of national key monitoring and rational use drug (1 st NKMRUDs), National Health Commission of the People's Republic of China release the 2 nd NKMRUDs to further strengthen reasonable use of drugs. Unfortunately, 2 nd NKMRUDs include some drugs of National Volume-based Procurement and National Essential Medicines, which challenges the management of pharmaceutical affairs on the three kinds of drugs.Objective: To investigate the prevalence of 2 nd NKMRUDs and explore their monitoring indicators.Methods: An adapted WHO methodology for point prevalence surveys was conducted for the 2 nd NKMRUDs. For the monitoring indicators, we sought to explore whether defined daily dose (DDD) and days of therapy (DOT) can be suitable for 2 nd NKMRUDs through comparing differences between DDD and DOT with the prescribed daily dose (PDD).Results: Among the 935 included patients, 29.20% of the patients received at least one of 2 nd NKMRUDs. A total of 273 patients were administered with 487 times of 2 nd NKMRUDs.Among them, 162 patients, 62 patients, and 49 patients were receiving one, two, and three or more agents, respectively. The most commonly prescribed 2 nd NKMRUDs were compounded amino acid, budesonide, ceftazidime. The total DDDs and DOTs of the 2 nd NKMRUDs were 3360.68 and 1819.80, respectively, with the PDDs of 1865.26. The deviations (80.17%) of DDDs from PDDs was significantly greater than those (-2.44%) of DOTs.The prevalence of 2 nd NKMRUDs was obtained by using adapted PPS methodology at a tertiary university hospital. DOT indicator is found to more accurately reflect actual consumption than DDD indicator for 2 nd NKMRUDs. It is recommend using DOT indicator to monitor 2 nd NKMRUDs.